Clinical impact of omega-3 consumption on the management of chronic heart failure - Mohammad, Marwan; Houmsse, Mahmoud (Ibnosina Journal of Medicine and Biomedical Sciences, 2017)
Interest in omega-3 has grown dramatically since the observation that Eskimos have a high level of omega-3 due to high fish consumption that was associated with a low incidence of myocardial infarction. This was thought to be related to its antithrombotic effect due to inhibition of platelet aggregation. Subsequently, several studies indicated a potential beneficial impact of omega-3 in the treatment and prevention of cardiovascular disease including chronic heart failure (CHF) especially in patients with reduced ejection fraction. Despite the progress in the medical and device management of CHF, a significant number of patients with this clinical syndrome do not respond to current therapy. In addition, CHF remains a condition of a high morbidity, hospitalization and mortality. Therefore, clinicians got interested in exploring any potential benefit in the care of patients with CHF. Potential benefits of omega-3 in the management of CHF patients have been evaluated and showed possible positive effect on the progression of CHF through several mechanisms. These include the improvement of endothelial function, reduction of vascular tone, reduction of platelet aggregability, and improvement of myocardial function. This review article cites data from several experiments pertaining to the benefits of omega-3 in patients with CHF. The aim is to review the mechanisms, potential benefits, and possible therapeutic implications of omega-3 in patients with CHF. Results show that there is a significant difference in patients who intake omega-3 versus those who do not. This article is proof that there are other methods to treating CHF than what is prescribed in modern medicine.
Keywords: Chronic heart failure; Omega-3; platelet aggregation; arrhythmia